FAMILY FACTORS AND THE "FUTURE" OF UNSCHOOLED TEENAGERS: OVERVIEW AND DETERMINANTS IN THE COMMUNE OF TCHAOUROU (BÉNIN) - Lucien Médard DAHOUE; Judicaël ALLADATIN (Universitaria Publishing House, Craiova, 2022)
The situation of unschooled teenagers in the labor market seems particularly worrisome. This study is related to concerns about the social integration of adolescents and aims to identify the determinants of the future of out-of-school adolescents in the commune of Tchaourou. It specifically addresses, through a nested multinomial logit regression, two aspects of the "future" of adolescents outof-school: economic activity and future plans. The results show that the size of the household of residence and the financial support granted by parents/guardians are the key factors in the exercise of an income-generating activity by out-of-school adolescents. The future of adolescents out-of-school are significantly influenced by the relationship with the head of the household, the standard of living of the household and the type of household.